CURRENT PERSPECTIVES ON THE SUBJECT OF PUBLIC HEALTH AND HEALTH CARE - Dildora Ergashevna Kushmatova; Honbuvi Khakimovna Khakimova (Scholar Express Journals, 2022)
Public health and health care management as a science and a subject of teaching in medical higher education institution takes the leading place in the health care system of the country and in training of future doctor.
Keywords: : Public health and health care management; medical universities; socio-economic factors